Factors associated with disabling low back pain among nursing personnel at a medical centre in Japan: a comparative cross-sectional survey - Takahiko Yoshimoto; Akatsuki Kokaze; Hiroyuki Oka; Shuhei Ishikawa; Shingo Muranaga; Ko Matsudaira (BMJ Open)
Objectives Low back pain (LBP) is a common cause of disability among nursing personnel. Although many studies regarding the risk factors for LBP among nursing staff have focused on the physical load at work, multidimensional assessments of risk factors are essential to identify appropriate preventive strategies. We aimed to investigate the association of multidimensional factors (individual, physical, psychological and occupational) with disabling LBP among nursing personnel in Japan.Design Observational study with comparative cross-sectional design.Setting Data were collected using the self-administered questionnaire at a tertiary medical centre.Participants After excluding participants with missing variables, 718 nursing personnel were included in the analysis.Outcome measures A self-administered questionnaire assessed individual characteristics, rotating night shift data, severity of LBP, previous episode of LBP, sleep problem, kinesiophobia (Tampa Scale for Kinesiophobia), depressive condition (K6), physical flexibility and frequency of lifting at work. A logistic regression model was used to evaluate the factors associated with disabling LBP (LBP interfering with work) among nursing personnel.Results Of all participants, 110 (15.3%) reported having disabling LBP. The multivariable logistic regression analysis after adjustment for several confounding factors showed that kinesiophobia (highest tertile, adjusted OR (aOR): 6.13, 95% CI : 3.34 to 11.27), previous episode of LBP (aOR: 4.31, 95% CI: 1.50 to 12.41) and insomnia (aOR: 1.66, 95% CI: 1.05 to 2.62) were significantly associated with disabling LBP.Conclusions The present study indicated that kinesiophobia, a previous episode of LBP, and sleep problems were associated with disabling LBP among nursing personnel. In the future, workplace interventions considering assessments of these factors may reduce the incidence of disabling LBP in nursing staff, although further prospective studies are needed.